Hierarchically designed hybrid nanoparticles for combinational photochemotherapy against a pancreatic cancer cell line. Issue 7 (6th February 2018) - Joubert, F.; Pasparakis, G.
Abstract : Hierarchical formulation of hybrid nanoparticles that consist of aggregated gold nanoparticles impregnated into a gemcitabine–polymer conjugate matrix for photochemotherapy of pancreatic cancer. Abstract : Here, we report the formulation of hybrid nanoparticles consisting of aggregated gold nanoparticles (GNPs) impregnated into a gemcitabine–polymer conjugate matrix that exhibit synergistic photo-chemo-therapeutic activity against pancreatic cancer. Well-defined, sub-100 nm hybrid NPs were successfully formulated and their photothermal conversion efficiency was evaluated, which was found to be as high as 63% in the red-visible spectrum. By varying the GNP and GEM–polymer feed, it was possible to control the red-shifting of the surface plasmon resonance at therapeutically relevant wavelengths. The hybrid NPs exhibited significant cytotoxicity against MiaPaCa-2 cells with a half-maximal inhibitory concentration (IC50 ) of 0.0012 mg mL −1 ; however the IC50 decreased by a factor of 2 after the cells were irradiated with a continuous wave red laser for 1 min (1.4 W cm −2 ). Although the irradiation of the aggregated GNPs loaded in the hybrid NPs produced a higher thermal effect for the same amount of non-loaded GNPs, the IC50 of the hybrid NPs was significantly lower than that of the free GNPs, hence indicating a synergistic effect of the polymer bound GEM and the GNPs.